2023
DOI: 10.1002/aenm.202301597
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Engineering of P‐Block Metal‐Based Catalysts Toward Industrial‐Scale Electrochemical Reduction of CO2

Abstract: The efficient conversion of CO2 to value‐added products represents one of the most attractive solutions to mitigate climate change and tackle the associated environmental issues. In particular, electrochemical CO2 reduction to fuels and chemicals has garnered tremendous interest over the last decades. Among all products from CO2 reduction, formic acid is considered one of the most economically vital CO2 reduction products. P‐block metals (especially Bi, Sn, In, and Pb) have been extensively investigated and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 247 publications
0
17
0
Order By: Relevance
“…It is well-known that mass transfer of CO 2 RR in H-type cells is limited, while the current density is hard to approach industrially relevant levels (>200 mA cm –2 ). , Therefore, the activity and stability of Bi-DC was assessed in a three-compartment configuration flow cell employing a Bi-DC-modified gas diffusion electrode, where the three-phase reaction interface offered the possibility of overcoming limitations of mass transfer and achieving high current density (Figure a). Since CO 2 combined with a large amount of OH – to form carbonate leading to carbon loss, and the formed carbonate accumulated in the GDE pores blocked the diffusion of reactant CO 2 , these problems were currently difficult to be solved in a strongly alkaline electrolyte (1 M KOH), although strongly alkaline electrolytes had the advantages of low solution resistance and fast ionic conduction as well as inhibition of the HER .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that mass transfer of CO 2 RR in H-type cells is limited, while the current density is hard to approach industrially relevant levels (>200 mA cm –2 ). , Therefore, the activity and stability of Bi-DC was assessed in a three-compartment configuration flow cell employing a Bi-DC-modified gas diffusion electrode, where the three-phase reaction interface offered the possibility of overcoming limitations of mass transfer and achieving high current density (Figure a). Since CO 2 combined with a large amount of OH – to form carbonate leading to carbon loss, and the formed carbonate accumulated in the GDE pores blocked the diffusion of reactant CO 2 , these problems were currently difficult to be solved in a strongly alkaline electrolyte (1 M KOH), although strongly alkaline electrolytes had the advantages of low solution resistance and fast ionic conduction as well as inhibition of the HER .…”
Section: Resultsmentioning
confidence: 99%
“…The p-block metals (Pd, In, Sn, and Bi), with the last valence electron located at the outermost p-shell layer (ns 2 np 1 to ns 2 np 3 ), show an excellent performance in the generation of HCOOH/formate via the electrochemical CO 2 reduction reaction (CO 2 RR) due to the unique properties such as low ionization energy and high electronegativity. , Also, due to the tunable oxidation states of p-block metals, it is highly versatile in the formation of p-block metal-based compounds at various valence levels. It has been shown that the activities of Pd, In, and Sn catalysts are oxygen-dependent and a strong yet positive correlation between CO 2 RR performance and oxygen content in materials at the electrode/electrolyte interface exists .…”
Section: Introductionmentioning
confidence: 99%
“…However, the theoretical results of metallic Bi, Pb, and PbO electrodes do not match the experimental reaction trends. Despite the unknown effects of surface oxygen of these electrodes at the operating potential, the active sites could also be derived from the surface atom vacancies, the functional groups, or the edges of a special morphology. …”
Section: Resultsmentioning
confidence: 99%
“…11 P-block metals, such as bismuth (Bi), indium (In), tin (Sn), and lead (Pb), have been widely recognized as efficient catalysts for selective HCOOH generation. 12 Among them, Bi has attracted more attention due to its decent performance, low toxicity and high Earth abundance. 13 However, there is still a lot of room to improve the activity and selectivity of Bi-based catalysts because the weak binding energy of the key intermediate *OCHO limits their catalytic performance.…”
Section: Introductionmentioning
confidence: 99%